Answer:
Step-by-step explanation:
(g-f)(x) = 9x³ - 4x² + 10x - 55 - [ 4x³ +3x² - 5x + 20]
To remove the parenthesis, take - inside, multiply f(x) by -1
= 9x³ - 4x² + 10x - 55 - 4x³ - 3x² + 5x - 20
Now, bring like terms together,
= 9x³ - 4x³ - 4x² - 3x² + 10x + 5x - 55 - 20
= 5x³ - 7x² + 15x - 75
Answer:
⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️WARNING THE VIRUS LINK POSTER JUST POSTED A LINK FULL OF 20 VIRUSES IN IT DONT CLICK IT⚠⚠⚠⚠⚠⚠⚠☠⚠️
⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️Step-by-step explanation:
⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️⚠☠⚠️
⚠☠⚠️⚠☠⚠️
#include <stdio.h> #include <stdlib.h>
// Function to perform division (x / y) of two numbers x and y. // without using division operator in the code. int divide(int x, int y)
{ // handle divisibility by 0. if (y == 0)
{ printf("Error!! Divisible by 0"); exit(1);
} // store sign of the result.
int sign = 1; if (x * y < 0)
Answer:
y=
−3
/2
x+
9/
2
Step-by-step explanation:
Let's solve for y.
9x+6y=27
Step 1: Add -9x to both sides.
9x+6y+−9x=27+−9x
6y=−9x+27
Step 2: Divide both sides by 6.
6y
/6=−9x+27
/6
y=
−3
/2
x+
9/
2
Answer:
y=
−3
/2
x+
9/
2
Answer:
5
Step-by-step explanation:
2-7=5